The Country of Sexualised Children: Whiteness, Innocence, and the "Sexualisation of Childhood". Issue 3 (3rd July 2018) - Thompson, Jay Daniel
ABSTRACT: This article argues that the sexualisation of childhood discourses have a distinct history in Australia. To advance this argument, I will explore the similarities between these discourses and discourses surrounding the iconic Australian "lost child". In all of these discourses, a white child (here a symbol of White Australia's future and past) becomes lost in an unforgiving and dangerous environment. This child is assumed to be asexual, though with the likelihood that they will mature into reproductive heterosexuality. This latter point will be illuminated in the final section of the article, which will focus specifically on the 2016 criticisms of the Safe Schools Coalition Australia. These criticisms are the most recent examples of anti-sexualisation discourses in Australia.